A 5-year neutralizing immune response to yellow fever vaccine in HIV-infected and HIV-uninfected adults. (1st February 2022) - Durier, Christine; Mercier-Delarue, Séverine; Verdière, Nathalie Colin De; Meiffrédy, Vincent; Matheron, Sophie; Samri, Assia; Resch, Martine; Marchand, Lucie; Autran, Brigitte; Launay, Odile; Simon, François
Abstract : Supplemental Digital Content is available in the text